INCREASING OF THE SUPEROXIDE DISMUTASE TOTAL ACTIVITY IN MICROGLIAL CELLS UNDER THE TREATMENT BY RIBES NIGRUM L. ALCOHOL EXTRACT (Proceedings of the YSU B: Chemical and Biological Sciences, 2020)
Cell redox homeostasis is formed as a result of the balance between the accumulation of reactive oxygen species and functioning of the antioxidant enzymes or non-enzymatic antioxidants. The alcohol extracts from the leaves of Ribes nigrum L. were prepared to investigate the antioxidant activity and protective effects against both BV-2 microglial wild type (WT) cells and acyl-CoA oxidase type 1 (ACOX1) deficient cell (ACOX1–/–) lines․ Our investigations showed that R. nigrum extracts possess remarkable antiradical activity in 1-diphenyl-2-picrylhydrazyl (DPPH) with IC50 value of 32.7±0.8 µg·mL–1. 3-(4,5-dimethyltrazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assay showed that the sub-cytotoxic concentration of R. nigrum extract in both cases was 1 mg·mL–1. The further treatment of microglial cells with the mentioned concentration of extract brought the remarkable increasing (up to 350%) of activity of the total superoxide dismutase (SOD) – the core antioxidant enzymes, under the treatment during the 48–72 h. So, relaying on the obtained data it is possible to insist that the lack of ACOX1 can be compensated by the activation of cell enzymatic antioxidant defense mechanisms.
Keywords: $Ribes$ $nigrum$; antiradical activity; microglial cells; superoxide dismutase